The Impact of the Trump Doctrine on Syria - Salih Omar Issa; Chenar Babaker Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
United States foreign policy has sought to maintain primacy on the global stage, but every U.S. president has maintained U.S. foreign policy in their own context. Counter to previous administrations, President Donald Trump has focused U.S. foreign policy through the lens of transactional realism concentrating on counterterrorism and challenges to U.S. interests and allies in the Middle East. Trump has criticized his predecessors for their policies of deep engagement leading to a deterioration of U.S. ‘Greatness,’ wasted tax dollars, and wasted American lives. Rooted in his background as an entrepreneur, President Trump has centered foreign policy around “America First.” However, U.S. interests in Syria are complicated by a multitude of actors involved in the Syrian conflict. Consequently, President Trump utilizes smart power with limited engagement in Syria based on cooperation with regional and international actors, particularly with regards to the ‘War on Terror.’ This strategy focuses on working with Russia, even if concessions are necessary, to curb Iran’s role in the region while protecting longtime ally, Israel. Furthermore, the United States exerts